Медикаментозне лікування ішемії за синдрому діабетичної стопи - Горобейко, М. Б. (Clinical Endocrinology and Endocrine Surgery, 2014)
Conducted to study the effectiveness urokinase for the treatment of patients with a TcPO 2 within 20- 30 mm Hg in cases of diabetic foot syndrome. Research Group – RG – (25 patients) received 1,0-0,05 million IU/day of urokinase for 20-26 days. Control Group – CG – (11 patients) – recruited retrospectively. Estimated dynamics of fibrinogen, TcPO2 and dynamics of ulcer healing (assessed by the beginning of treatment, at 10 and 20 days). In RG dynamics of fibrinogen was as follows – 4,15±1,16 g/l at the begin-ning of treatment, at 10 and 20 days – 2,96±1,31 g/l and 1,94±0,31 g/l, respectively. Decreasing is significant. It is also significant the difference between RG and CG during and after treatment (fibrinogen levels in CG from beginning 3,56±0,67 g/l and 3,12±0,68 g/l in the end. The difference in the CG is statistically nonsignificant. Just significantly improved level TcPO2 in RG (from 23,44±2,25 to 33,20±5,96 mm Hg). Compared to the dynamics in the CG (22,36±1,37 mm Hg in beginning and 22,73±1,81 mm Hg at the end of treatment) in the RG dynamics was signifi-cantly better. The average area of the ulcer at the beginning of treatment in the RG was 2,70±1,13 sq cm in 10 days – has decreased, but not significantly to 2,26±1,02 sq cm, and 20 days later – 1,41±0,94 sq cm – the difference is significant with exponents 0 and 10 days. Thus, demonstrated the efficacy of urokinase on the healing of ulcers in patients with DFS through a reduction in fibrinogen levels and improve blood circulation in the lower limbs.